Structural style of the Chos Malal fold and thrust belt, Neuquén Basin, Argentina: relationship between thick- and thin-skinned tectonics - Sánchez, Natalia Paola (2015)
The Chos Malal fold and thrust belt is a thick-skinned mountain belt that deformed the Mesozoic deposits of the Neuquén Basin during the Andean orogeny. Four structural cross-sections across the entire deformed area, supported by field and subsurface data, suggest a strong link between the thick and thin-skinned structures. Major Andean thrusts detached ~12 km into the crust produced large basement wedges, which were inserted in the cover producing minor order structures. The westernmost of these wedges is exposed forming the Cordillera del Viento, while a second basement slice was interpreted from seismic lines. Both thick-skinned structures transferred deformation to the cover along the Auquilco Formation and contribute to create all the thin-skinned structures surveyed the fold and thrust belt. We recognized half-graben geometries in the seismic lines, which preserve their extensional configuration and the main normal faults are not inverted compressively. Shortenings calculated from the restoration of the cross-sections are 15.6 km (28%), 15.8 km (28.3%), 14.16 km (26.5%) and 15.7 km (28.18%) for the north, centrals and south cross-sections respectively, which evidence a homogeneous contraction during the Andean orogeny in this segment of the Chos Malal fold and thrust belt.